Analysis of Human Resource Management Processes in the Procurement and Utilization of Community Health Center Employees as BLUDs at UPTD Community Health Centers in Bulungan Regency, North Kalimantan Province - Sunardi; Ratna Wardani; Joko Prasetyo (Green Publisher Indonesia, 2026)
This research aims to analyze the human resource management process in the procurement and utilization of employees at Community Health Centers (Puskesmas) with Regional Public Service Agency (BLUD) status in Bulungan Regency, North Kalimantan Province. The study uses a descriptive qualitative approach, with data collection techniques consisting of in-depth interviews, observation, and documentation involving the head of the community health center and related structural officials. The results show that human resource planning is carried out systematically to balance service needs with the availability of health workers through workload analysis and competency requirement projections. Human resource organization has been based on regulations from the Ministry of Health and the Health Office, with a clear division of authority through the organizational structure and job descriptions. Guidance is carried out with an emphasis on discipline, two-way communication, motivation, and performance-based incentives. HR control is implemented through monitoring and evaluation mechanisms that cover performance, discipline, and the application of rewards and sanctions. However, several obstacles were identified, such as limited human resources, high workloads, multiple job assignments, and limited technological infrastructure. Overall, the results of this study confirm that the HR management process at the Bulungan BLUD Community Health Centers has been carried out based on the principles of efficiency, accountability, and service quality improvement. However, it still requires strengthened coordination and greater utilization of information technology so that HR management becomes more adaptive and sustainable.